2021
DOI: 10.1080/10494820.2020.1863232
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and concerns for real-time online classes: focused on the security and privacy issues

Abstract: As education is increasingly going online, propelled by the COVID-19 outbreak, how to build student engagement has become critically important, and it is, therefore, necessary to explore the motivators and barriers to student engagement comprehensively. Given the nature of an online learning environment, this study specifically focused on security and privacy concerns as the major issues that may be restricting student engagement. Based on the data collected from 296 students studying at Y University, South Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 73 publications
(104 reference statements)
2
17
0
Order By: Relevance
“…Therefore, they did not consider technology itself a problem. Privacy concerns derived from the use of cameras were mentioned by a significant number of those surveyed, in line with other research works, such as [ 25 , 35 , 36 , 37 ], and were consistent with the concerns derived from the use of videoconferencing [ 59 , 60 , 61 ]. More specifically, when talking about their privacy concerns, the students pointed out diverse comments as follows: “Many students do not want to show their personal space”; “The camera show your house to unknown people”; “it is invasive”; “violates your privacy”; “you cannot totally control what happens in your place of study” or “you lose privacy since the whole world can see your room and what you do”.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, they did not consider technology itself a problem. Privacy concerns derived from the use of cameras were mentioned by a significant number of those surveyed, in line with other research works, such as [ 25 , 35 , 36 , 37 ], and were consistent with the concerns derived from the use of videoconferencing [ 59 , 60 , 61 ]. More specifically, when talking about their privacy concerns, the students pointed out diverse comments as follows: “Many students do not want to show their personal space”; “The camera show your house to unknown people”; “it is invasive”; “violates your privacy”; “you cannot totally control what happens in your place of study” or “you lose privacy since the whole world can see your room and what you do”.…”
Section: Discussionsupporting
confidence: 86%
“…Strong student-to-student and student-to-instructor interaction top the ranking of the list of positive elements highlighted by the undergraduates surveyed in terms of mention index while appearing as a negative element for a group of students in line with [ 9 , 36 ]. This dichotomy in terms of perception could be explained depending on what were the students’ references when comparing SC: ERT or F2F, as shown in [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some participants stated that they felt more secure and confident in group activities in online classes as they were not being listened to or observed by others. This finding is in parallel with some other studies like Kim (2021). In these studies, it was emphasised that crating small groups in online classes might foster students' motivation and autonomy, particularly for communication activities.…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that two types of privacy concerns (abuse and unauthorized access to private data) affected students’ perceptions of knowledge hiding and negatively influenced their participation in collaborative learning online. Kim (2021) has conducted an insightful study examining the factors that motivate and hinder Reserve Officers’ Training Corps (ROTC) students from participating in online courses. Their results indicated that perceived usefulness and peer behavior directly affect participation intentions.…”
Section: Introductionmentioning
confidence: 99%